2021
DOI: 10.31261/tapsla.8594
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based Differences in EFL Learners' Language Learning Strategies and Productive Vocabulary

Abstract: Gender is a key factor in the field of Second Language Acquisition (SLA), where its impact on language learning strategies (Aslan, 2009; Oxford & Nyikos, 1989; Sumarni & Rachmawaty, 2019) and productive vocabulary (Canga Alonso & Arribas García, 2014; Fleckenstein, 2018; Jiménez Catalán & Moreno Espinosa, 2004) has been investigated. However, to our knowledge, there is a lack of research of gender on language learning strategies in relation to productive vocabulary in English as a Foreign Langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…All information was available in websites; they just needed to type the keywords, and all explanations would be presented (Respondents 6,7,18,20,42,55,61,63,74). Although female respondents use language learning significantly more than males, there is significant difference between them regarding productive vocabulary (Montero-SaizAja, 2021).…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…All information was available in websites; they just needed to type the keywords, and all explanations would be presented (Respondents 6,7,18,20,42,55,61,63,74). Although female respondents use language learning significantly more than males, there is significant difference between them regarding productive vocabulary (Montero-SaizAja, 2021).…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 88%
“…On the other hand, gender disparities may also be related to the cultural, social, and educational context in which a foreign language is learned. (Montero-SaizAja, 2021). Hence, the researcher wishes to find the answer of several questions related to adult women's challenges of English proficiency test based on the cultural, social, and educational context namely:…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%
“…To fulfill the objectives, a quantitative questionnaire survey was conducted to collect data. The quantitative research design was widely used in studies on LLS use and its relationship with gender and proficiency (Alrashidi, 2022;Damanik, 2022;Montero-SaizAja, 2021). This design is also suitable to achieve the present study's aim because it enables to explore means of variables and differences between means of different gender or proficiency groups, and thereby helps reveal the frequency of participants' LLS use and the differences of LLS use frequency related to gender as well as proficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Jiao and Simon (2022) applied Oxford's theory to examine the LLS use of 269 Chinese EFL learners and achieved similar research findings. Oxford's (1990) theory has also been used in studies on the correlation between LLS use and certain individual factors, including gender and language proficiency, which have been considered decisive in learners' use of LLS (Bećirović et al, 2021;Montero-SaizAja, 2021). Most research on the influence of gender on LLS use has revealed significant differences in strategy use between female and male language learners (Bećirović et al, 2021;Jiao & Simon, 2022;Zhou & Intaraprasert, 2015a).…”
Section: Literature Review Language Learning Strategymentioning
confidence: 99%
“…The impact of gender on language learning strategies has been examined in the field of Second Language Acquisition ( Oxford and Nyikos, 1989 ; Griffiths, 2003 ; Aslan, 2009 ; Nguyen and Godwyll, 2010 ; Sumarni and Rachmawaty, 2019 ; Melvina Lengkanawati and Wirza, 2020 ; Montero-SaizAja, 2021 ; Dinsa et al, 2022 ). Oxford and Nyikos (1989) reported that females utilized cognitive, metacognitive, and social strategies more frequently than males in their study of undergraduate learners of foreign languages.…”
Section: Literature Reviewmentioning
confidence: 99%